Central Role for MyD88 in the Responses of Microglia to Pathogen-Associated Molecular Patterns - Nilüfer Esen; Tammy Kielian (2006)
Abstract Microglia, the innate immune effector cells of the CNS parenchyma, express TLR that recognize conserved motifs of microorganisms referred to as pathogen-associated molecular patterns (PAMP). All TLRs identified to date, with the exception of TLR3, use a common adaptor protein, MyD88, to transduce activation signals. Recently, we reported that microglial activation in response to the Gram-positive bacterium Staphylococcus aureus was not completely attenuated following TLR2 ablation, suggesting the involvement of additional receptors. To assess the functional role of alternative TLRs in microglial responses to S. aureus and its cell wall product peptidoglycan as well as the Gram-negative PAMP LPS, we evaluated primary microglia from MyD88 knockout (KO) and wild-type mice. The induction of TNF-α, IL-12 p40, and MIP-2 (CXCL2) expression by S. aureus- and peptidoglycan-stimulated microglia was MyD88 dependent, as revealed by the complete inhibition of cytokine production in MyD88 KO cells. In addition, the expression of additional pattern recognition receptors, including TLR9, pentraxin-3, and lectin-like oxidized LDL receptor-1, was regulated, in part, via a MyD88-dependent manner as demonstrated by the attenuated expression of these receptors in MyD88 KO microglia. Microglial activation was only partially inhibited in LPS-stimulated MyD88 KO cells, suggesting the involvement of MyD88-independent pathways. Collectively, these findings reveal the complex mechanisms for microglia to respond to diverse bacterial pathogens, which occur via both MyD88-dependent and -independent pathways.